Membangunkan sistem perolehan data berintegrasi kos rendah untuk pemantauan struktur kejuruteraan - Ibrahim, Abdul Fatah (2015)
Nowadays, the development of technology in the field of structural deformation is tremendous. Various techniques and equipment are used in monitoring works for engineering structure. Sensors such as the Global Positioning System (GPS) and accelerometer have a great potential for application in the study of engineering structural displacement, especially in bridge monitoring. Therefore, the aim of this study is to develop an interfacing program using a LabVIEW software that involves the integration of GPS receiver and accelerometer with Compact RIO-9022 (CRIO) embedded real-time controller. Sensor integration with LabVIEW program was developed and implemented to realize the data collection and structural monitoring system. The LabVIEW software which employed graphical programming was used as a platform to develop an interfacing program for the integration of GPS and accelerometer instruments for structural monitoring system. The program is very user-friendly and easy to handle for real time monitoring system. The capabilities and performance of the LabVIEW interface program were also investigated in the simulation test on rigid structure. From the study, the program is capable to show the data in real-time from observation. The analyses that were performed to the observed data from the simulated structure vibration have proved that deflection in the longitudinal, lateral and height directions are able to be detected.